Changes in anaphylaxis trends and characteristics in emergency department admissions in Türkiye: From 2015 to 2021 based on the Ministry of Health database - Elif Soyak Aytekin, MD; Seda Şirin, MD; Esra Kıratlı Nalbant, MD; Naim Ata, MD; Ahmet Sertçelik, MD; Mustafa Mahir Ülgü, MD; Şuayip Birinci, MD; Koray Harmancı, MD; Zülfikar Akelma, MD (World Allergy Organization Journal)
Background: The incidence of anaphylaxis is increasing worldwide. However, there is a lack of data on anaphylaxis trends in Türkiye. This study aims to analyse trends in anaphylaxis-related emergency department (ED) visits and examines factors associated with fatal anaphylaxis in Türkiye. Methods: We retrospectively analyzed data from Türkiye's Ministry of Health database from 2015 to 2022. Codes from the International Classification of Diseases, 10th revision (ICD-10), were used to identify anaphylaxis. Results: During the study period, a total 21,370 ED admissions for anaphylaxis were identified, and anaphylaxis admissions increased 1.23-fold from 3.90 to 4.79 per 105 population per year. The anaphylaxis trigger was unknown in 79.9% of cases, followed by drugs (11.7%), food (5.7%) and venom (2.7%). Epinephrine was administered in 49.6% of cases, and a total of 424 patients (2.1% of total cases) died. The frequency of intensive care unit (ICU) hospitalization increased 6.0-fold from 2015 to 2021, and age-adjusted average-weighted mortality rate for anaphylaxis was 0.66 per million. Older age, presence of asthma, and ICU hospitalization were found to be significantly associated with fatal anaphylaxis (p < 0.001 for all). Frequencies of death were 9.1% for venom anaphylaxis, 1.2% in drug anaphylaxis, and 0.2% for food anaphylaxis. Epinephrine autoinjector (EAI) was prescribed for 6.9% of all patients. Conclusions: This is the first study of ED admissions for anaphylaxis using a large, nationwide data from Türkiye. Increasing numbers of ED admissions, ICU hospitalizations and mortality show that anaphylaxis is an important public health issue in Türkiye.